The influence of religiosity on high risk behaviour among trainess of National Service Training Center (PLKN) in Pasir Mas, Kelantan and Besut, Terengganu - Musa, Marliana (2015)
The adolescent period is considered to be difficult and challenging for both children and their parents’ particularly in biological, emotional, cognitive and psychological aspects. Many researchers interested in the topic of adolescent with high risk behavior due to its potential negative consequences in adult life and religiosity appeared to be one of the protective factors. Adolescents who were more religiouswere found to be protected from involved with high risk behavior based on many previous studies. Objectives: This study wasaimed to determine the prevalence of high risk behavior and the level of religious personality among trainees of national service training center (PLKN) in Pasir Mas, Kelantan and Besut, Terengganu as well as to determine the association between high risk behavior and level of religiosity. Methodology: A cross sectional study, using a convenience sampling method conducted from October 2014 to February 2015 involving 347 trainees.A self-rated questionnaire regarding personal information, high risk behavior and sexual behavior was distributed together with Muslim Pesonality Scale (Maruzairi H. et al 2015, unpublished), a validated Malay version Religious Personality Scale of Muslim Religious-Personality Inventory (MRPI). Data analysis was done using Statistical Package for the Social Sciences (SPSS) version 22 by usinglogistic regression, an independent t test and multiple linear regression (MLR) to see the association between high risk behavior, socio-demographic and level of religiosity. Results: Among the study population, 64.8% were male and 35.2% were female. The majority of them staying with their parents and had income less than RM1000. The prevalence of high risk behavior was 43.8% for smoking, alcohol use was 7.5% and illicit drug use was 8.4%. Prevalence of pornography, masturbation and sexual intercourse experienced were 54.8%, 49.0% and 15.0% respectively. Logistic regression analyses showed that factor of the trainees being taken care by other than their parents were associated with alcohol use, illicit drug use and had sexual intercourse experience premaritally. Gender factor was associated with pornography viewing behavior. 24.2% of the trainees had high religious personality, 62.0% had moderate and 13.8% had low religious personality. In MLR, trainees who had a pornography experience (p=0.033) and sexual intercourse experience (p=0.001) were significantly associated with the lower level of religiosity. Conclusion: Religiosity is known to be a protective factor towards high risk behavior especially sexual related behavior. This study support that adolescent involve with pornography viewing and premarital sexual intercourse had lower level of religiosity compared to adolescent without pornography viewing and premarital sexual intercourse. However, since the challenges during an adolescent developmental period is high, religiosity should be strengthened continually with other factors such as parental guide, moral value and knowledge of high risk behaviors.